(untitled) (Port Harcourt Medical Journal, 2017)
Background: Gastrointestinal stromal tumour are rare gastrointestinal tumour that probably originate from the interstitial cells of Cajal and 95% express a specific molecular marker. They occur most commonly in the stomach (60%) followed by the small intestine (30%) and may present with gastrointestinal bleeding. Case Report: A 40year old man presented with passage of frank blood per rectum with associated haemodynamic instability necessitating several units of blood transfusion. Following adequate resuscitation, lower and upper GI endoscopy done were negative and subsequently had emergency laparotomy for continued gastrointestinal bleeding. We found a bleeding ileal tumour which was resected. Histopathology confirmed gastrointestinal stromal tumour. Conclusion: small bowel stromal tumour rarely and unusually presents with massive lower GI bleeding. Diagnosis may be delayed due to inaccessibility of the small bowel to routine upper and lower GI endoscopy. Mesenteric angiography, radionuclide RBC, capsule endoscopy, push enteroscopy depending on the fitness of the patient, may aid diagnosis. Prompt surgical resection and adjuvant imatinib therapy for malignant variants is the treatment of choice. Keywords: Difficult diagnosis, massive gastrointestinal haemorrhage, stromal ileal tumour